A metal hybrid bistable composite tube for multifunctional and reconfigurable antenna. (1st March 2023) - Guo, Xiangwei; Lin, Shu; Dai, Fuhong
Abstract: The bistable composite is a deformable lightweight structure with two stable states, which are widely used in aerospace and space fields as deployment mechanisms and deformable structures. In this paper, a new application is proposed as an omnidirectional and directional radiation reconfigurable antenna based on a bistable composite tube. The antenna is prepared based on carbon fiber composite (CFRP) and glass fiber composite (GFRP) as the substrate and metal as the antenna layer co-cured. Mechanical behavior and material micro-interface analyses of the bistable structures are performed. Antennas of different materials and different layups are fabricated and analyzed. The results indicate that the designed antenna structure can be stabilized in the unfolded or stowed state without external support, unfolded into an omnidirectional antenna, and stowed into a directional antenna. The electromagnetic analysis is simulated and experimented to verify its performance as a multifunctional and reconfigurable antenna. Meanwhile, this bistable antenna possesses many advantages, including its lightweight, high storage ratio, and rapid reconfiguration, which make it an excellent candidate for satellite and spacecraft antennas. Graphical abstract: A bistable structure is a lightweight composite that can be deformed and has two stable forms. It is widely used in aerospace and space applications, mainly as a deployment mechanism and deformable structure. A new application direction is proposed, which is used as a multifunctional and reconfigurable antenna. The designed antenna has an ultra-high storage ratio and is ultra-lightweight because it uses carbon fiber composite materials. Due to the first design of a bistable antenna tube, the mechanical and electromagnetic properties of different fiber materials, and layups are simulated and experimentally analyzed, respectively. The results show that the designed metal hybrid antenna tube has two variable stable configurations, and the antenna energy radiation direction map and operating frequency can be switched. Meanwhile the structure can be expanded or stored within 1s. Configuration B is an ultra-wideband antenna with a bandwidth of 1 GHz. By controlling the parameter changes, the antenna frequency can be widened and used within the required range. Besides, the state B can reach a high storage ratio. The structure can be assembled on spacecraft and satellites as a versatile stowable and deployable antenna. Image 1 Highlights: A bistable composite antenna tube with two stable forms, which can transform into each other quickly. The omnidirectional/directional patterns and operating frequency of the antenna can be switched. The multi-function antenna is lightweight and can reach a high storage ratio. Different composites and metal layups are studied to analyze their different mechanical and electromagnetic properties.